PERAN PEMERINTAH DAERAH DALAM MEMBERIKAN PERLINDUNGAN HUKUM TERHADAP KEBERADAAN PASAR TRADISIONAL DI KOTA SEMARANG - Alif Adibatul Lathifah; Widayati Widayati (UNISSULA Semarang, 2018)
Traditional market is the embryo of the beginning of the economy in Indonesia. But lately the traditional market seems to be eroded by the emergence of an increasingly modern market. Competition seems to occur clearly between these two markets, especially in the city of Semarang which is the number of modern markets are increasingly mushrooming. The existence of City Regulation No. 9/2013 Semarang which regulates the traditional market is expected traditional markets still exist in the modern era that has emerged modern market.In this study discusses the current condition of traditional markets in the midst of the emergence of modern markets in Semarang City and How the role of local governments in providing legal protection against the existence of traditional markets in the city of Semarang By using sociological juridical research methods, is expected to observe directly the implementation of the Act / Regional Regulations that have been established by the Local Government of Semarang City with the reality in practice. Researchers in this case make a direct observation about the trading process in the traditional market of Semarang City. The results showed that the economic activity in Traditional Market is slightly disturbed by the emergence of modern market in Semarang City. And with such conditions the traditional market usually makes a strategy to stay competitive with Modern Market. Traditional market conditions in the city of Semarang is still far from expected, the impression of slums, less regular arrangement is still found in the traditional market of Semarang City. And the government of Semarang city is still not maximized when giving sanctions against the economic actors who violate the rules that have been set.Keyword: The Role of Semarang City Government, Traditional Market